Análisis de la incidencia de la financiación del órgano de control institucional sobre la calidad del gasto público en la Municipalidad Distrital de San Juan Bautista, periodo 2014 – 2020 - Alencar Reátegui, Neforis Estefania (2024)
The institutional control body (OCI), according to the Peruvian legal framework, is in charge of carrying out government control in a public entity or institution. In the case of the Municipality of the San Juan Bautista district, Maynas province, there is also such a control unit. Taking this into consideration, in this thesis it is proposed to investigate what is the impact that the financing of this control body may have on the behavior of the quality of public spending executed in the district Municipality of San Juan Bautista, considering a time horizon reflected from from 2014 to 2020. For this purpose, the present study uses the appropriate statistical and econometric methodology represented by the calculation of correlation and determination coefficients, as well as the estimation of a linear model by means of ordinary least squares. . At work, the main results obtained are that the degree of variation generated by OCI financing on the quality of public spending is 2.83 percent if such financing were to increase by 1 percentage point; however, this incidence is not significant since a p-value of 0.16 was obtained, which is higher than 0.05.